2015
DOI: 10.2471/blt.14.139998
|View full text |Cite
|
Sign up to set email alerts
|

Legislation coverage for child injury prevention in China

Abstract: ObjectiveTo examine the extent to which effective interventions to prevent unintentional child injury are reflected in the laws and regulations of China.MethodsWe focused on the six common causes of fatal child injuries – drowning, road traffic injury, falls, poisoning, burns and suffocation. We investigated 27 interventions recommended by the United Nations Children’s Fund, the World Health Organization or the European Child Safety Alliance. We searched China National Knowledge Infrastructure and Lawyee for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 8 publications
0
32
0
1
Order By: Relevance
“…A 2015 review of legislative coverage for child injury prevention in China reported that no law covered interventions to prevent child drowning deaths. There is no national programme to teach children to swim 57. Anecdotally few Chinese people can swim, though no published reports of swimming ability were identified.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 review of legislative coverage for child injury prevention in China reported that no law covered interventions to prevent child drowning deaths. There is no national programme to teach children to swim 57. Anecdotally few Chinese people can swim, though no published reports of swimming ability were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries, such as motor vehicle accidents, drowning, poisoning, falls, fire, and violence, affect school-aged children worldwide (Carruth et al, 2010). Li et al (2015) suggested that school-based health programs provide support for the positive effects of injury prevention and that the regulation of laws at the government level is required.…”
Section: Discussionmentioning
confidence: 99%
“…When unintentional injuries occur, the initial steps of emergency care depend on the first responders' ability to provide first aid. The outcome of an unintentional injury often depends on the care that is provided at the time of the injury (Gresham et al, 2001;Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nivel internacional se identifica que el sector de la salud es uno de los más afectados tanto por los problemas en la asignación de recursos disponibles como por la carencia o ineficiencia de las estrategias de intervención y mecanismos de gestión orientados a traer soluciones integrales a los problemas de salud. Por su relevancia se destacan los estudios de (Carvajal, 2007;O'Brien et al, 2014;Li et al, 2015;Fialová, 2014;Hernández & Vega, 2014). En Cuba instituciones como el Ministerio Nacional de Salud Pública y el Centro Nacional de Educación Sexual (CENESEX) lideran las campañas preventivas nacionales.…”
Section: Objeto De Estudiounclassified